Pengaruh Kompetensi, Integritas dan Koordinasi terhadap Efektivitas Kerja Anggota Dewan Perwakilan Rakyat Daerah Kota Tangerang Selatan - Bastian, Ricky Yuanda; Rangkuti, Zulkifli; Pratikno, Yuni (Perhimpunan Sarjana Ekonomi dan Bisnis, 2024)
The Influence of Competence, Integrity and Coordination on the Work Effectiveness of Members of the Regional People's Representative Council of South Tangerang City. The work effectiveness of council members is not yet optimal in the Regional People's Representative Council (DPRD) of South Tangerang City. Integrity, competence and coordination factors dominantly influence the work effectiveness of board members. This research aims to analyze the magnitude of the influence of competence, integrity and coordination on the work effectiveness of members of the South Tangerang City Regional People's Representative Council. The research approach applied is quantitative, namely research that emphasizes analysis on numerical data or numbers obtained using statistical methods. This research uses survey methods and explanatory/causal analysis. The sample was members of the South Tangerang City DPRD, namely 50 members of the Council. Analysis using multiple linear regression analysis. The results of the analysis show that there is a significant influence of competence, integrity and coordination on the work effectiveness of members of the Regional People's Representative Council of South Tangerang City, both individually and simultaneously.